Political Violence and Narratives. A Subjective Dimension - Herrera, Martha Cecilia; Olaya, Vladimir (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The time has come for memory. This current phrase in Colombia suggests the positioning of recent political violence issues in the public agenda, which has triggered the development of academic research as well as the design of public policies that aim at the clarification of events related to the armed conflict and their possible solutions. From this horizon, this paper analyzes the importance of biographical and testimonial literature, and its pertinence to historical research on political violence. In order to do so, we analyze one of the testimonial narratives collected in a research project regarding the configuration of subjectivities in contexts of political violence, and indicate how this type of resources both empower the ordinary subject as participant of a given historical moment and reveal the close bond between individual and society.